Firsthand learning through intent participation - Rogoff,Barbara (2004)
This article examines how people learn by actively observing and "listening-in" on ongoing activities as they participate in shared endeavors. Keen observation and listening-in are especially valued and used in some cultural communities in which children are part of mature community activities. This intent participation also occurs in some settings (such as early language learning in the family) in communities that routinely segregate children from the full range of adult activities. However, in the past century some industrial societies have relied on a specialized form of instruction that seems to accompany segregation of children from adult settings, in which adults "transmit" information to children. We contrast these two traditions of organizing learning in terms of their participation structure, the roles of more- and less-experienced people, distinctions in motivation and purpose, sources of learning (observation in ongoing activity versus lessons), forms of communication, and the role of assessment.